O Programa Nacional de Suplementação de Ferro na ótica das gestantes e dos nutricionistas no município de Cabedelo - PB - Barrêto, Sheilla Virgínia Silva Nascimento (2012)
Iron deficiency anemia is an important public health problem, being children, women of childbearing age and pregnant women the most vulnerable biological groups. The National Iron Supplementation, coupled with mandatory fortification of wheat flour and corn flour with iron and folic acid and nutritional guidance, constitute the set of strategies aimed at controlling and reducing the problem in Brazil. The objective of this research was comprise that program in the city of Cabedelo - Paraíba, analyzing the knowledge of pregnant women and nutritionists about the activities, the conduct of intervention and the nutrients involved. There were also the difficulties faced and the most recurrent complaints that limited the program's actions and continuity of beneficiaries in supplementation. It is a participatory evaluation study, in which interviews were conducted with structured qualitative and quantitative approaches, using open and closed questions and registration of personal data and socioeconomic data, obtained from medical records and cards accompanying the pregnant women in pre-scheduled visits, in the days of prenatal 19 Units of Family Health of the city. Study subjects were 172 pregnant women and 10 nutritionists responsible for the running of the program. How criteria of inclusion, we considered whether women with complete data, using at least one of the supplements offered by the program (ferrous sulfate and / or folic acid) and were not at the first prenatal visit. Closed questions have generated tables of absolute and relative frequency simple. To analyze the open questions, extracted the central idea of the answers, grouping them into categories and themes of analysis were coded to perform the absolute frequency distribution of responses. Regarding the statistical analysis, we used the computational tool Statistical Package for the Social Sciences, version 19.0. The study was approved by the Research Ethics Committee of the University Hospital Lauro Wanderley, Federal University of Paraíba, under protocol number 548/10. It was observed that few pregnant women know the program and its activities. The answers of women who said they know him as the varied activities that nutritionists developed and those experienced by pregnant women. Most of the beneficiaries reported correctly follow the periodicity and the time of intake, as recommended by professionals. Both the interviewees differed in responses regarding the length of stay in supplementation. The women knew better functions than those of iron and folic acid also more food source of this mineral than the vitamin in question, while nutritionists had a great knowledge of the subject. The forgetfulness and drug reactions in the opinion of the pregnant women and the lack of the supplements on the units, for both study subjects were alluded to as the main reasons for interruption of supplementation. Therefore, the evaluation of the National Iron Supplementation in Cabedelo, in a participatory vision of the actors involved, allowed a better understanding of its operation, while it showed the limitations encountered and possible improvements led to its implementation in the city.